A case report of retroperitoneal infection following TROPIS surgery - Liang Xiaoxia; Lin Jian; Zhang Heng; Su Dan; Ren Donglin (结直肠肛门外科)
The transanal opening of intersphincteric space (TROPIS) is a new surgical procedure for the treatment of complex anal fistula. This procedure involves accessing the fistula through the anus, using an electrocautery knife to incision the mucosa and internal sphincter above the fistula between the sphincters without disconnecting the external sphincter. All fistulas are thoroughly scraped clean, and the infection on both sides of the external sphincter is cleared. TROPIS has the advantages of simple surgical operation, rapid healing of the postoperative wound, less patient pain, and good recovery of anal function, making it worthy of clinical promotion. However, there are few reports in the literature regarding postoperative complications and specific treatment measures for TROPIS. Our team has treated a rare case of retroperitoneal infection (a rare complication) following TROPIS surgery. We report the treatment process and complication management plan here for communication with colleagues.